TAX LEARNING INNOVATION: UPGRADING CRITICAL THINKING AND SELF-EFFICACY LEVEL OF PROSPECTIVE TAX CONSULTANTS - KUSUMANINGRUM, NURCAHYANING DWI; Sari Dewi Poerwanti; Nurina Adi Paramitha; Sukron Makmun (Cattleya Darmaya Fortuna, 2024)
Prospective tax consultants must have competent critical thinking skills. However, critical thinking skills and self-efficacy levels for prospective tax consultants are still low. The problem-based learning (PBL) model has been widely implemented to improve students' critical thinking skills and efficacy. However, weaknesses were found, such as the need to increase self-efficacy and investigative processes based on scientific process skills. Therefore, innovation was created to develop scientific critical thinking (SCT). Learning model based on the strengths and weaknesses of the PBL model. This innovation is also supported by theory and empirical studies. This study functions as a preliminary study in the process of developing the SCT learning model to improve the critical thinking skills and self-efficacy of prospective tax consultants. This research includes needs analysis, a literature review, and a field survey. The results show that innovation can serve as a basis for developing a hypothetical SCT learning model. The syntactic SCT learning model includes: student orientation, scientific activities, presentation of the results of scientific activities, critical completion of thinking tasks, and evaluation. The hypothetical SCT learning model must be tested to meet the aspects of validity, practicality, and effectiveness to improve the critical thinking skills and self-efficacy of tax consultant candidates.